Effect of sacubitril/valsartan on sinus rhythm maintenance after catheter ablation in patients with persistent atrial fibrillation without reduced ejection fraction heart failure: a study protocol for a multi-center, open-label, randomized, controlled, superiority clinical trial - Qiu, Ruowu; Ni, Qingqing; Wu, Muli; Xiao, Zhongbo; Xiao, Jiaxin; Lin, Weizhao; Huang, Weipeng; Chen, Yequn; Chen, Chang; Hong, Liekai (Frontiers in Cardiovascular Medicine, 2024)
A high recurrence rate of atrial fibrillation was monitored after catheter ablation for persistent atrial fibrillation.Sacubitril/valsartan can improve outcomes for patients with heart failure and ventricular tachycardia, but few studies examined whether it can reduce recurrence or improve cardiovascular outcomes in patients with persistent atrial fibrillation after catheter ablation. In this study, we will assess the effect of sacubitril/valsartan on sinus rhythm maintenance and incidence of major adverse cardiovascular events (MACE) in patients with persistent atrial fibrillation after catheter ablation through a randomized controlled trial (RCT).Methods: This is a multi-center, randomized, controlled, open-label, superiority clinical trial involving 462 patients without reduced ejection fraction heart failure after catheter ablation of persistent atrial fibrillation. Patients will be randomized to (1) receive the standard treatment strategy plus sacubitril/valsartan titration, or (2) receive the standard treatment strategy without taking sacubitril/valsartan. The primary outcome will be sinus rhythm maintenance rate over 12 months, monitored by random electrocardiogram and 24-hour Holter electrocardiogram.Discussion: This study is designed to evaluate the effect of sacubitril/valsartan on sinus rhythm maintenance and incidence of major adverse cardiovascular events (MACE) in patients with persistent atrial fibrillation after catheter ablation. The results will evaluate sacubitril/valsartan as a novel treatment for improving prognosis and a complement to conventional drug therapy.Trial registration: Registered with Chinese Clinical Trials Registry on 27 August 2022，identifier: ChiCTR2200062995.